2022
DOI: 10.1111/trf.17216
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function of whole blood after short‐term cold storage: A prospective in vitro observational study

Abstract: Background There is no standardized storage temperature of whole blood for acute normovolemic hemodilution (ANH). Study Design and Methods We conducted a prospective observational study to examine the difference in platelet function between short‐term whole blood storage at 4 and 22°C. Venous blood (40 ml) was collected from seven healthy subjects who gave prior written consent. The samples were divided into three groups: before storage (group Pre), cold (4°C) storage (group C), and room temperature (22°C) sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…It was found that platelets released approximately 50% β‐TG when stored at room temperature for more than 5 days [30]. Cold storage of whole blood for 6 h will cause platelet aggregation and the release of more β‐TG and PF4 [31]. The reason for the reduction in β‐TG release in the 24‐PTW group was thought to be because the β‐TG release from frozen platelets decreases along with the reduction in the activation function of platelets.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that platelets released approximately 50% β‐TG when stored at room temperature for more than 5 days [30]. Cold storage of whole blood for 6 h will cause platelet aggregation and the release of more β‐TG and PF4 [31]. The reason for the reduction in β‐TG release in the 24‐PTW group was thought to be because the β‐TG release from frozen platelets decreases along with the reduction in the activation function of platelets.…”
Section: Discussionmentioning
confidence: 99%
“…ANH is considered as a safe and effective blood conservation technique [ 18 ]. First, unlike preoperative autologous blood donation, it is not needed to collect autologous blood repeatedly and save it for several days before surgery in the ANH group [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…21 While ANH-collected blood stored at room temperature for up to 8 hours has a hemostatic effect, 22 preserving it at 4 °C helps maintain platelet activity. 23 In our study, we used a 4 °C refrigerator to maximize blood clotting function preservation. Transfusing fresh whole blood can partially enhance coagulation function.…”
Section: Discussionmentioning
confidence: 99%